Learning Strategy of The Quran and Hadith in Forming Religious Character at MTs Ma'arif Bumi Baru, Blambangan Umpu District, Way Kanan Regency - Hakim, Muhamad Rouful; Jaenullah, Jaenullah; Prasetiawati, Eka (International Journal on Advanced Science, Education, and Religion, 2025)
This study discusses the learning strategy of the Al-Qur'an Hadīth subject in forming the religious character of students at MTs Ma'arif Bumi Baru, Blambangan Umpu District, Way Kanan Regency. The background of this study is based on the importance of religious character education amidst the moral and social challenges faced by the younger generation. The Al-Qur'an Hadīth subject has a strategic role in instilling deep Islamic values, so that learning is not only oriented towards mastering the material, but also on forming attitudes and behaviors that reflect religious values. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews with teachers and students, and documentation of learning activities. The results of the study show that teachers use several effective strategies, including: integration between religious theory and practice, habituation of daily worship such as dhuha prayer, recitation of the Al-Qur'an before the lesson begins, instilling the values ​​of honesty, responsibility, and discipline through studying the meaning of the verses of the Al-Qur'an, and the application of the exemplary method (uswah hasanah) in daily interactions. In addition, the use of discussion methods and contextual reflection of values ​​encourages students to relate the teachings of the Qur'an and Hadith to everyday life. This strategy has been proven to be able to improve students' religious character as reflected in politeness, enthusiasm for worship, honesty, and enthusiasm for sharing. Thus, learning the Qur'an and Hadith which is designed holistically and integratively can be an effective medium in forming students' religious character. This study recommends that this learning strategy continue to be developed and supported by the madrasah environment and family in order to create a generation that is faithful, has noble character, and is responsible.